Kontribusi Usaha Gogos Terhadap Pendapatan Rumah Tangga - Aadila, Ade Esti; Sideng, Uca; Hasriyanti, Hasriyanti (LaGeografia, 2021)
This study aims to determine: 1) How is the socio-economic condition of gogos traders in Jalange, Mallawa Village, Mallusetasi District, Barru Regency, 2) How big is the contribution of gogos business to household income in Jalange, Mallawa Village, Mallusetasi District, Barru Regency. The population in this study were all households engaged in gogos business in Jalange, Mallawa Village, totaling 37 families. The sample in this study amounted to 37 people because the population is less than 100. This research is a descriptive study. The results showed 1) the socio-economic condition of the people who worked selling gogos, namely the age of 39-43 years as much as 29.71%, graduated from high school as much as 45.95%. The livelihoods of respondents apart from gogos were various, including entrepreneurs, private workers, construction workers, farmers and fishermen. The majority of the household income of gogos sellers in Jalange, Mallawa Village is Rp. 1,000,000. The highest income from the sale of gogos is Rp. 2,500,000 per month and the lowest is Rp. 500,000 per month. 2) The contribution of gogos business to household income which makes gogos the main job reaches 100% for 5 units of gogos sellers and the highest contribution is for households that make gogos as an alternative to increasing household income reaching 59%. This shows that gogos has a fairly large role in increasing household income